Diffusion Kurtosis Imaging Shows Similar Cerebral Axonal Damage in Patients with HIV Infection and Multiple Sclerosis. Issue 3 (30th January 2018) - Buyukturkoglu, Korhan; Fleyser, Lazar; Byrd, Desiree; Morgello, Susan; Inglese, Matilde
ABSTRACT: BACKGROUND AND PURPOSE: In this pilot study, we sought to investigate the pathological changes in the white matter (WM) of medically complex, combination antiretroviral therapy (cART)‐treated patients with human immunodeficiency virus (HIV), comparing them to patients with long‐standing, secondary progressive multiple sclerosis (SPMS). METHODS: Using diffusion kurtosis imaging (DKI)‐derived WM tract integrity (WMTI) metrics, 15 HIV and 15 age‐ and sex‐matched SPMS patients with similar disease duration underwent magnetic resonance imaging analysis. Maps of WMTI metrics were created. Tract‐based spatial statistics analysis of the whole brain and regions of interest analysis of the corpus callosum (CC) and the anterior thalamic radiations (ATRs) were performed and the derived WMTI metrics were compared between the groups of patients. RESULTS: Axonal water fraction, an index of chronic axonal loss, showed similarities between HIV and the chronic MS patients in all regions; in contrast, tortuosity, a measure more sensitive to myelin loss, was regionally variable. In addition, in HIV patients, WMTI metrics of the CC and left ATR were associated with cognitive test scores, suggesting clinical relevance for these measures of WM damage. CONCLUSIONS: We conclude that DKI‐derived WMTI metrics may be a valuable tool in assessing the WM changes of medically complex HIV‐infected individuals. While not powered to examine potential etiologies of WM changes in this pilot sample, regional variations in WMTI metrics were seen. When contrasted with changes consequent to chronic MS of similar duration, HIV and its comorbidities appear to result in similar degrees of axonal damage, but regionally variable amounts of myelin loss and extraxonal abnormality.